H19 promotes pancreatic cancer metastasis by derepressing let-7’s suppression on its target HMGA2-mediated EMT - Ma, Chenchao; Nong, Kate; Zhu, Hongda; Wang, Weiwei; Huang, Xinyu; Yuan, Zhou; Ai, Kaixing (Tumor biology, 2014)
The long noncoding RNA (lncRNA) H19 has been recently characterized as an oncogenic lncRNA in some tumors. However, the role of H19 in pancreatic ductal adenocarcinoma (PDAC) remains unclear. In this study, we found that not only the levels of H19 was overexpressed in PDAC compared with adjacent normal tissues, but also H19 expression was upregulated remarkably in primary tumors which subsequently metastasized, compared to those did not metastasis. Subsequently, the efficacy of knockdown of H19 by H19-small interfering RNA (siRNA) was evaluated in vitro, and we found that downregulation of H19 impaired PDAC cell invasion and migration. We further demonstrated that H19 promoted PDAC cell invasion and migration at least partially by increasing HMGA2-mediated epithelial-mesenchymal transition (EMT) through antagonizing let-7. This study suggests an important role of H19 in regulating metastasis of PDAC and provides some clues for elucidating the lncRNA-miRNA functional network in cancer.